Development of spatial and interdisciplinary research in the Russian regions - Bilczak, Wasyl (Rozwój przestrzennych i interdyscyplinarnych badań w regionach rosyjskich, 2019)
The article discusses the interdisciplinary approaches to the study of regional economic systems and an integrated approach to the theory and methods of spatial development in spatial progress analysis. In addition, the administrative and the reproduction approaches of scientists to the assessment of specific territorial entities are analysed. Attention is paid to the manifestation forms of the reproduction stages with a complete cycle. Examples of specific national systems’ development and political institutions are considered ed, and also the important processes directly impacting on the regionalization are highlighted. For example, economic disciplines characterize the region as spatial, socio-economic integrity, where the main processes of material production take place and the integrity of the reproduction base is preserved. The approaches of various scientific disciplines in the research on regional economic systems and specific recommendations for their development are shown
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 7-17
Keywords: interdisciplinary research; complex research; regional economics systems; spatial development; territorial development; region; regionalization; badania interdyscyplinarne; badania kompleksowe; systemy regionalno-gospodarcze; rozwój przestrzenny; rozwój terytorialny; regionalizacja